Internal Controls' Impact on Sacco Performance In Uganda: : A Case Study of Rukiga Sacco - Agaba Moses; Turyasingura John Bosco; Kabagambe Jesse David (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose: This investigation on the performance of Rukiga SACCO's internal controls was conducted in the Rukiga District. The study's goals were to examine the impact of segregation of duties on Rukiga SACCO's performance, determine the impact of independent checks on that performance, and assess the impact of risk management on that organization's financial performance. Methodology: The study was carried out after the cross-sectional survey. Data from 135 respondents were collected, and quantitative and qualitative analyses were carried out. Since descriptive analysis requires the presentation of a single variable and its properties, frequency tables were used to represent the data. The bivariate correlations between the predictor components and the dependent variable were examined using a Pearson correlation matrix. A linear regression model was used to fit the data. Results/Findings: According to research results from the regression model, segregation of duties (R=762), independent checks (R=676), and risk management (R=899) have a beneficial influence on the performance of Rukiga SACCO in Rukiga District. The main finding of this study is that the performance of Rukiga SACCO is greatly impacted by risk management, separation of roles, and independent checks. Limitations: The structured questionnaire, which was administered by the participant themselves, served as the primary data collection tool. The likelihood of non-responses was anticipated because the researcher loses control of the questionnaire once it is submitted to respondents; this could have an impact on data analysis and generalizability. Yet, in order to guarantee a majority response, the researcher set up follow-up operations. Contribution: Task segregation, independent auditing, and risk management are advised to be given more attention in order to achieve loan portfolio expansion, profitability development, and market share increase, which are crucial elements of Rukiga SACCO's performance in Rukiga District